2005
DOI: 10.1097/01.sap.0000134751.73260.3a
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Angiosarcoma After Mastectomy and TRAM Flap Breast Reconstruction

Abstract: Radiation-induced angiosarcoma of the breast is being reported with increasing frequency as a result of the increased use of radiation therapy in conjunction with breast conservation surgery. However, this entity has not been well documented in patients undergoing mastectomy. The authors present a case of angiosarcoma occurring in a patient 6 years after undergoing mastectomy for invasive duct carcinoma with immediate transverse rectus abdominis musculocutaneous flap reconstruction followed by postoperative ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
0
20
0
2
Order By: Relevance
“…All 7 patients died within six to 36 months after RIS diagnosis [13]. Most authors did not found any evidence of benefit after chemotherapy in RIS patients [3]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All 7 patients died within six to 36 months after RIS diagnosis [13]. Most authors did not found any evidence of benefit after chemotherapy in RIS patients [3]. …”
Section: Discussionmentioning
confidence: 99%
“…The development of secondary neoplasm is of particular importance, especially sarcomas in women previously treated with radiation therapy [2]. Case reports [3, 4] and the publications of large series of important oncology centers [5] or registers [6] is a consequence of the increasing frequency of this type of secondary neoplasms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographic aid in the diagnosis of secondary angiosarcoma has been reported to be limited (1,6,10). We present three cases of secondary breast angiosarcoma that developed in the setting of prior breast irradiation to illustrate its various radiologic presentations and discuss how the presence of certain imaging findings might assist in recognition of these tumors.…”
mentioning
confidence: 99%
“…Although the risk of developing breast sarcoma after breast reconstruction is exceedingly rare, the prevalence of these sarcomas will increase as patients live longer due to advances in surgical and radiation therapy [38]. A few case reports have described sarcomas in the reconstructed breast [39, 40]. The imaging features of these sarcomas are similar to those of sarcomas that develop in the native breast tissue [41], with the exception of secondary angiosarcoma that tends to affect the skin [42].…”
Section: Malignant Imaging Findings After Autologous or Implant-basedmentioning
confidence: 99%